LANGUAGE AND CULTURE IN THE NOVEL 'DARK HORSE' (International Journal of Food and Nutritional Sciences, 2022)
The language of human society moves forward at its own pace, carrying civilization, conduct,thoughts and culture. Although it is also true that the environment also has a great impact on language. Butin natural circumstances, man's language, knowledge, beliefs, customs, art, craft, philosophy, literature,rules and regulations, value system, lifestyle, social institutions, religious rituals, festivals, attitude towardsothers and all the things related to these come together, which form a specific system. When Santosh, thehero of ‘Dark Horse’, comes to Delhi for the first time, he reaches Mukherjee Nagar of his dreams. Theauthor has called Santosh the dark horse. There is a dark horse inside us too, what is needed is the will tokeep it running. At the end of the novel, the author gives the analogy of a dark horse to the readers bysaying who will be the next dark horse, maybe it is you. Similarly, this is the story of every strugglingstudent who leaves their homes to achieve success and comes into the wider world. Dark Horse is astruggle-filled but true picture. The problems arising in the preparation of the exam, the struggle of thestudents at all levels, the struggle of food, intellect and spontaneity, from the lifestyle to the language, thereis also the struggle of purity and rusticity. Coming from the village, the compromise with the urban cultureis mostly shown. There is a struggle in the dialogue between father and son. Overall, the best part of thisbook is the language. Which many people will not like. The author is very honest towards the language ofthe book. It has been kept very natural, the language is Hindi which takes us to Bihar and Uttar Pradesh.Which may hurt some people. Overall, this is a successful novel.